Análise da gestão de resíduos da construção civil no estado do Paraná e município de Cascavel-PR - Vargas , Carolline (2018)
The civil construction sector generates an expressive volume of solid waste, in general, such waste does not always have adequate management, being deposited in improper places, and consequently compromising the quality of the environment. In this sense, it is important to know the local, regional and national reality, for analysis of the management of the Waste of Civil Construction (RCC), checking the positive and negative aspects, allowing to contribute to the formulation of public policies, which to assess these aspects. In this sense, this research is justified, which has as central objectives, to analyze the state of the art of the management of the waste of civil construction in the state of Paraná and in the municipality of Cascavel-PR, in order to contribute with the scientific community to knowledge of the current reality, in addition to identifying the relevant legislation and the management processes, with the future aim of subsidizing actions and strategic planning, which aims at the sustainability of the civil construction sector, with regard to the aspects social, environmental and economic. For the scope of the proposed objectives, descriptive methodology was used, through bibliographical research and data collection, in addition to the mixed method, which consists in the collection and analysis of qualitative and quantitative data, the results evaluated in a way Integrated. The results showed that within the state of Paraná, 60% of municipalities present specific legislation for the implementation of the Waste Management Plans of Civil Construction (PGRCC), and that 92.6% of the localities still earmarked the RCC to landfills With the rest of the municipal waste, or disposal in improper locations. In the municipality of Cascavel-PR, the surveys in the construction sites pointed out some negative aspects in the management of the RCC, such as the lack of training of the employees responsible for the works, irregular disposal of the RCC, as well as absence of supervision of the competent bodies for further final approval of the PGRCC. The analysis of the results obtained made it possible to conclude the difficulty of obtaining precise data and that in this sense new studies and diagnostics are fundamental to the knowledge of the reality in its entirety, moreover, in the municipality of Cascavel-PR, it is made the improvement of the management tools of the existing RCD.